The Prevalence of Female Contraception in a Zero-Growth Population Policy - Umi Listyaningsih; Wiwik Puji Mulyani; Dwi Lestari (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2024)
This study aims to describe why couples decide to have unmet needs and the impact on the family and the country of these decisions. The study used mixed methods. Qualitative, qualitative and secondary data analysis (quantitative). The results of the study High unmet need does not always lead to high fertility. Education, high female labor participation, and female empowerment are among the supporting factors. Independent women have a unique perspective in interpreting children. Women have the capacity to decide and analyze the presence of children. When a child is considered a burden on the family, it will be limited to have children. There's a group that identifies themselves as unmet need, but the TFR rate in a region remains stable. The willingness to spread children apart, or not have more children, and sexual intercourse without contraceptives have high no-birth outcomes. The conclusion is that not all unmet need contributes to a high TFR. Sexual intercourse without contraceptives, and still making TFR stable can be a new discourse for reproductive health issues of the people who use it.This study aims to describe why couples decide to have unmet needs and the impact on the family and the country of these decisions. The study used mixed methods. Qualitative, qualitative and secondary data analysis (quantitative). The results of the study High unmet need does not always lead to high fertility. Education, high female labor participation, and female empowerment are among the supporting factors. Independent women have a unique perspective in interpreting children. Women have the capacity to decide and analyze the presence of children. When a child is considered a burden on the family, it will be limited to have children. There's a group that identifies themselves as unmet need, but the TFR rate in a region remains stable. The willingness to spread children apart, or not have more children, and sexual intercourse without contraceptives have high no-birth outcomes. The conclusion is that not all unmet need contributes to a high TFR. Sexual intercourse without contraceptives, and still making TFR stable can be a new discourse for reproductive health issues of the people who use it.